The Replication of Retail Fashion Formats into Foreign Countries: A Qualitative Analysis - Schröder, Christoph (Springer, 2015)
Christoph Schröder does one of the first attempts to analyze format transfers within the scope of different strategies, format elements, countries and success with focus on the fashion industry. Three distinct format transfer strategies are identified. The empirically observed design of format elements supports and extends the existing research. Fashion firms standardize their “Retail culture”, which acts as a foundation for a successful format transfer strategy (core elements). New insights are provided with regard to format transfer into foreign countries as well as over a timeframe of five years. International retailers face specific challenges with regard to the decision on their retail format abroad, which is known as an important success driver. They may transfer their format elements unchanged or may adapt those elements. One successful strategy is known to be an unchanged format replication, which is linked to the fashion industry.